Peranan Raden Ajeng Kartini Terhadap Kemajuan Perempuan Di Daerah Kalimantan Timur - Isnawati S.H., M.H (Prodi Ilmu Administrasi Negara, 2016)
This research is going to know the role of R.A. Kartini to encourage the women in Indonesia in participating thedevelopment of Indonesia. The method of the research isdiscriptive-kualitative where the data is collected by libraryresearch, observation and spreading quetioneair. It takes 3 (three) months to collect the data by reading the literature, observation, interview and sending quesionairs. In collecting data by literature is in the library of the University of 17 Agustus 1945 Samarinda. In observation is carried out in the offices of either private or state officers in Samarinda. In interview the researcher asks to some women in the University of 17 Agustus 1945 Samarinda. In sending the questionairs the researcher to some women. The results o the researh are (1). The name of R.A. Kartini is not so popular at this moment (2). Most of the respondents are not familiar with the efforts of R.A. Kartini to encourge the women in Indonesia, (3). Some adminres R.A. Kartini as the hero of Indoesian women, (4). Some women gives appreciation to R.A. Kartini’s letters to her friends as the excellent ideas. Relating the results, the reseacher suggets as follows (1). To give the information to the students about her by large sosialition by either written dan oral ones, (2). To celebrate the R.A. Kartini’s birtday by excellent performance, (3). To deepen the history lesson concerning some heroes.